Electrolyte minerals intake and cardiovascular health. Issue 15 (22nd August 2019) - Mohammadifard, Noushin; Gotay, Carolyn; Humphries, Karin H.; Ignaszewski, Andrew; Esmaillzadeh, Ahmad; Sarrafzadegan, Nizal
ABSTRACT: Appropriate intake of micronutrient, such as electrolyte minerals is critical for the well-being of the cardiovascular health system. However, there are some debates regarding the impacts of dietary and/or supplemental intake of these minerals, on the risk of cardiovascular events and associated risk factors. High sodium intake is adversely associated with the risk of hypertension. Although many reports refered to the positive association of Na intake and cardiovascular events and all-cause mortality, however, other studies indicated that low Na intake is related to higher risk of all-cause mortality and HF-related events. By contrast, dietary potassium, magnesium and calcium have an inverse correlation with cardiovascular events and risk factors, especially with blood pressure. There are some controversies about cardiovascular effects and all-cause mortality of high Ca intake, including no effect, preventive or adverse effect with or without vitamin D. Calcium supplementation might be beneficial for prevention of cardiovascular events and all-cause mortality only in individuals with low intake. Moreover, calcium intake showed a J- or U-shaped association with the risk of cardiovascular diseases. Due to the controversies of the effect of electrolyte minerals especially sodium and calcium intake on cardiovascular events, large scale, well-designed long-term randomized clinical trials are required to evaluate the effect of minerals intake on cardiovascular events and all-cause mortality. In this review, we discuss the role of dietary and or supplemental sodium, potassium, magnesium, calcium, in cardiovascular health, as well as their clinical applications, benefits, and risks for the primary prevention of cardiovascular disease, in general population.